Utilization of Interactive Learning Media Tutorial Models in Geographic Learning (Geographic Information System Learning) - Misdar Amdah; Dede Sugandi; Ahmad Yani (Journal of International Conference Proceedings (JICP), 2020)
The interactive learning media tutorial model is a computer-based learning media that has interactivity in it so that it involves the activeness of students in learning activities. The purpose of this research is to develop an interactive learning media application tutorial model that can help students improve their understanding of geographic information system learning materials. This research is a quasi-experimental study conducted at Watampone High School Class XII. The research subjects consisted of 33 students from 123 populations. The results showed that there was a significant increase in understanding of geographic information system material after learning using interactive media tutorial models with an average value after being given a pretest of 64.66 and after being given a posttest to 78, the average percentage increase was 36.05%.